2000
DOI: 10.1046/j.1365-2249.2000.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of mice with lipopolysaccharide (LPS) or IL-1β exerts dose-dependent opposite effects on Shiga toxin-2 lethality

Abstract: SUMMARYHaemolytic uraemic syndrome (HUS) has been closely associated with infection with a group of Shiga toxin-producing enterohaemorrhagic Eschericchia coli in young children. Shiga toxins (Stx) have been implicated as pathogenic agents of HUS by binding to the surface receptor of endothelial cells. LPS is a central product of the Gram-negative bacteria and several reports have documented that both LPS and Stx are important for disease development. In this study the reciprocal interactions between LPS and St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 39 publications
3
69
0
Order By: Relevance
“…Survival rates of BALB/c mice from Shiga toxin 2 were enhanced by 18-h pretreatment of either LPS or dexamethasone whereas only 1 h of LPS pretreatment decreased survival rates. This protection afforded by the 18 h LPS pretreatment condition was shown to be due to the increased endogenous corticosterone production secondary to LPS-induced IL-1 activation of the HPA axis (Palermo et al 2000). In these studies, the role of endogenous glucocorticoids in protection against Shiga toxin lethality was further supported by the decreased survival of adrenalectomized animals or those treated with the GR antagonist RU486.…”
Section: Bacterial Toxinsmentioning
confidence: 90%
“…Survival rates of BALB/c mice from Shiga toxin 2 were enhanced by 18-h pretreatment of either LPS or dexamethasone whereas only 1 h of LPS pretreatment decreased survival rates. This protection afforded by the 18 h LPS pretreatment condition was shown to be due to the increased endogenous corticosterone production secondary to LPS-induced IL-1 activation of the HPA axis (Palermo et al 2000). In these studies, the role of endogenous glucocorticoids in protection against Shiga toxin lethality was further supported by the decreased survival of adrenalectomized animals or those treated with the GR antagonist RU486.…”
Section: Bacterial Toxinsmentioning
confidence: 90%
“…It has previously been shown that Stx2 causes renal failure in mice (3,33,47). Having demonstrated that Stx2 does not directly affect the murine renal glomerular filtration barrier cells in vitro, we sought to determine the Stx2 target cells in the mouse kidney.…”
Section: Murine Glomerular Cells Do Not Express Gbmentioning
confidence: 99%
“…These studies indicate a synergistic effect of Stx and LPS in vivo, as has also been shown in vitro using endothelial cells (68). Other reports observed that pretreatment with LPS could either increase or decrease Stx2-induced lethality, depending on the dose and timing of injection and that the effects could be modulated by TNF-␣ or IL-1␤ (97). A recent publication (98) showed that antibodies to LPS block adherence of STEC to human intestinal epithelial cells in vitro, although the biologic significance of this finding has not been evaluated in vivo.…”
Section: Stec Virulence Factorsmentioning
confidence: 99%